2010
DOI: 10.1089/ten.teb.2009.0714
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells, Osteoblasts and Extracellular Matrix Proteins: Enhancing Cell Adhesion and Differentiation for Bone Tissue Engineering

Abstract: Cell adhesion to scaffolds has remained one of the challenges in tissue engineering. Although protein surface modification has been proven to enhance cell adhesion and retention, its specificity depending on cell and biomaterial types means that the best protein and concentration must be established for each specific application. This review focuses on the improvement of cell adhesion for human mesenchymal stem cells with an osteogenesis approach. A brief outline of the cell adhesion process and extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 75 publications
5
93
1
Order By: Relevance
“…Moreover, the introduction of PRF significantly improved the hydrophilicity and surface roughness of the scaffolds, which improved the seeding efficiency; this is consistent with other research, showing that the introduction of peptides onto polymer surfaces promoted cell adhesion. 57 In addition to enhance cell adhesion, the incorporation of PRF also promoted BMSC proliferation on the scaffolds, as indicated by toxicity and cell proliferation assays and SEM analysis at various time points, confirming that PRF provides suitable sites for cell attachment. Immunofluorescent staining and quantitative assessment suggested that BMSCs seeded on the scaffolds containing PRF expressed high levels of vinculin, confirming that the printed BCP/PVA/PRF scaffolds provide a favorable microenvironment for the adhesion, extension, and migration of BMSCs.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the introduction of PRF significantly improved the hydrophilicity and surface roughness of the scaffolds, which improved the seeding efficiency; this is consistent with other research, showing that the introduction of peptides onto polymer surfaces promoted cell adhesion. 57 In addition to enhance cell adhesion, the incorporation of PRF also promoted BMSC proliferation on the scaffolds, as indicated by toxicity and cell proliferation assays and SEM analysis at various time points, confirming that PRF provides suitable sites for cell attachment. Immunofluorescent staining and quantitative assessment suggested that BMSCs seeded on the scaffolds containing PRF expressed high levels of vinculin, confirming that the printed BCP/PVA/PRF scaffolds provide a favorable microenvironment for the adhesion, extension, and migration of BMSCs.…”
Section: Discussionmentioning
confidence: 64%
“…In particular, it has been shown that osteogenesis is strongly dependant on adhesion processes, involving matrix components such as type I collagen and OPN, as well as members of the integrin family, all required for the adhesion, migration, proliferation and differentiation of osteoblasts (Hidalgo-Bastida et al, 2010). Moreover, the involvement of specific integrins in the activation of the osteoblast-specific transcription factor RUNX2 has been demonstrated (Xiao et al, 1998).…”
Section: Research Articlementioning
confidence: 99%
“…al., 1968). Their studies demonstrated the existence of precursor mesenchymal cells, with the potential to differentiate into osteoblasts and fibrous tissue (Figure 2) (Charbord, 2010;Hidalgo-Bastida et al, 2010).…”
Section: Bone Marrow Stem Cellsmentioning
confidence: 99%
“…Accordingly, the safe and efficient clinical application of stem cells to bone tissue regeneration depends on the elucidation of mechanisms associated with senescence. Moreover, it is essential to understand the mechanisms of action and interaction with other cell types, with different biomaterials, soluble factors, extracellular matrix components (Hidalgo-Bastida et al, 2010) and biochemical and mechanical agents present in the microenvironment in vitro and in vivo, as well as to keep the proliferation of stem cells restricted to the implanted site and to know the gene control mechanism for safe induction of the desired functions (Gronthos et al, 2000;Discher et al, 2009). The identification of growth factors and the signaling mechanisms involved in the actual control of stem cell renewal and differentiation will allow the design of strategies to block senescence and to safely drive cellular differentiation (Satija et al, 2007).…”
Section: Stem Cells and Gene Therapy: Prospects Of Future Applicationsmentioning
confidence: 99%